Basic structural motif and major biophysical properties of Amyloid-beta are encoded in the fragment 18-35 - Chandrakesan, Muralidharan; Sarkar, Bidyut; Mithu, Venus Singh; Rajiv M. Abhyankar; Bhowmik, Debanjan; Nag, Suman; Sahoo, Bankanidhi; Shah, Riddhi; Gurav, Sushma; Banerjee, Raja; Dandekar, Sucheta; Jose, Jaya C.; et al. (Chemical Physics, 2013)
Aggregation and misfolding of the amyloid beta (A beta) peptide is thought to initiate Alzheimer's disease (AD). Here we study the role played by its central segment (A beta(18-35)) in determining these properties. A beta(18-35) has a solubility of 18 mu M. The soluble fraction consists mainly of small oligomers, which have mixed beta-sheet and random coil structures. The monomer is mostly a random coil with some residual compactness. Aggregated A beta(18-35) forms fibrils of width 3.0 +/- 0.7 nm, which is consistent with a hairpin shape. Each of these properties has a close similarity to A beta(40). Remarkably, solid state NMR indicates that the fibrils also retain the secondary structure and tertiary contacts of A beta(40). This is the shortest fragment of A beta reported so far which preserves its fibrillar architecture, including the hairpin turn, as well as its solution phase conformational properties. Residues 18-35 should therefore be a key target of AD therapeutics. (C) 2013 Published by Elsevier B. V.
Keywords: Alzheimer's disease; Fluorescence correlation spectroscopy; Protein aggregation; Solid-state NMR